Gut-brain axis and neurodegeneration: mechanisms and therapeutic potentials - Park, Kelly Jimin; Gao, Yao (Frontiers in Neuroscience, 2024)
This paper reviews the effects of gut microbiota in regulating neurodegenerative diseases through controlling gut-brain axis. Specific microbial populations and their metabolites (short-chain fatty acids and tryptophan derivatives) regulate neuroinflammation, neurogenesis and neural barrier integrity. We then discuss ways by which these insights lead to possible interventions - probiotics, prebiotics, dietary modification, and fecal microbiota transplantation (FMT). We also describe what epidemiological and clinical studies have related certain microbiota profiles with the courses of neurodegenerative diseases and how these impact the establishment of microbiome-based diagnostics and individualized treatment options. We aim to guide microbial ecology research on this key link to neurodegenerative disorders and also to highlight collaborative approaches to manage neurological health by targeting microbiome-related factors.